Primjena savremenih koncepata menadžmenta u funkciji unapređenja rada jedinica lokalne samouprave / Contemporary Managerial Concepts Apllication in Function of Upgrading Local Self Government Units Working (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Public administration is in the process of reforming that is taking place today in most countries in the world. The causes of these processes are the turbulent and dynamic development of the social system. The public administration reform is one of the strategic processes in the overall changes of national administrative systems, especially for transition countries. Bosnia and Herzegovina with its complex administrative structure faces in the process of transition the need for public administration reform. Public administration reform at all levels of government implies a new organizational design, because the current structure and organization is inefficient and ineffective. Necessary reforms are also one of the preconditions for entering into the European Union, which is a strategic priority. In line with the abovesated, it is necessary to know that reforms cannot be implemented without the application of modern management concepts in public administration organizations. In this regard, this paper is focused on of local self-government units researching capacities in the context of the intensity of applying contemporary management concepts with a particular focus on the ability to apply an integrated Balanced Concept for Balanced Scorecard (BSC) concept. The effectiveness of local self-government is viewed through five segments or five perspective of the Balanced Scorecard (BSC) concept. Businesses based on the principle of an equilibrium scorecard model enable successful development and implementation of a strategy that is causal-consequently related to the effectiveness of local self-government. The results of empirical research have confirmed that local self-governments that have developed perspectives of this model are more effective than those of local self-governments that have partially developed individual perspectives or do not have any developed at all from the perspective of the balanced scorecard model.
Keywords: Contemporary Management Concepts; Public Administration; Local Self-Government Units; New Public Management; BSC Application